Nanotube action between human mesothelial cells reveals novel aspects of inflammatory responses - Ranzinger, Julia; Rustom, Amin; Abel, Marcus; Leyh, Julia; Kihm, Lars Philipp; Witkowski, Margarete; Scheurich, Peter; Zeier, Martin; Schwenger, Vedat (PLOS ONE, 2011)
A well-known role of human peritoneal mesothelial cells (HPMCs), the resident cells of the peritoneal cavity, is the generation of an immune response during peritonitis by activation of T-cells via antigen presentation. Recent findings have shown that intercellular nanotubes (NTs) mediate functional connectivity between various cell types including immune cells - such as T-cells, natural killer (NK) cells or macrophages - by facilitating a spectrum of long range cell-cell interactions. Although of medical interest, the relevance of NT-related findings for human medical conditions and treatment, e.g. in relation to inflammatory processes, remains elusive, particularly due to a lack of appropriate in vivo data. Here, we show for the first time that primary cultures of patient derived HPMCs are functionally connected via membranous nanotubes. NT formation appears to be actin cytoskeleton dependent, mediated by the action of filopodia. Importantly, significant variances in NT numbers between different donors as a consequence of pathophysiological alterations were observable. Furthermore, we show that TNF-α induces nanotube formation and demonstrate a strong correlation of NT connectivity in accordance with the cellular cholesterol level and distribution, pointing to a complex involvement of NTs in inflammatory processes with potential impact for clinical treatment.